Pengaruh Laporan Segmen Terhadap Keputusan Investor - Yuniarwati, Elizabeth Sugiarto Dermawan, Melinda Haryanto (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2014)
This Study Investigates The Reaction Of Investors To The Segment Disclosures Presented In The Financial Statement Using Data Classification Condition: Full Sample Data, Non Traceable Income Data That Has Negative Income.